Stepping Beyond, In, and With JAEPL: Twenty Years of Hope - Kristie S. Fleckenstein (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
Treating readers to a detailed tour through JAEPL’s pages, the journal’s coeditor of 10 years touches on high points, also remembering the conference that initiated her relationship with its authors and readers.